The interaction between BRAF mutation and microsatellite instability (MSI) status in determining survival outcomes after adjuvant 5FU based chemotherapy in stage III colon cancer. Issue 8 (6th November 2018) - Chouhan, Hanumant; Sammour, Tarik; Thomas, Michelle L; Moore, James W
Abstract : Purpose: The predictive role of biomarkers in colon cancer is still being defined. The aim of this study is to determine the interaction between BRAF mutation and microsatellite instability (MSI) status in determining survival benefit after adjuvant 5‐FU based chemotherapy in stage III colon cancer. Methods: We performed a retrospective cohort study including all curatively resected stage III colon cancer cases over a 33‐year period. A clinicopathological database was collated (adjuvant chemotherapy, age, gender, obstruction, perforation, tumor location, grade, mucin, nodal stage, extramural vascular, and perineural invasion). BRAF (V600E) mutation testing was performed and MSI status established by immunohistochemistry for mismatch repair proteins and molecular testing for National Cancer Institute panel markers. Patients were categorized into four groups for comparison: MSS and BRAF−ve (termed " traditional "), MSI and BRAF−ve (termed " presumed Lynch "), MSI and BRAF+ve (termed " sporadic MSI "), and MSS and BRAF+ve (termed " other BRAF "). The primary endpoint was cancer specific survival. Interaction testing was conducted to determine whether there were different responses to chemotherapy between groups. Results: A total of 686 unselected cases met inclusion criteria and had tissue available, of which 15.7% had BRAF mutation (BRAF+ve) and 13.8% had MSI. Thirty‐nine percent received chemotherapy. Overall, adjuvant chemotherapy produced a cancer specific survival benefit (HR 0.66, 95% CI, 0.49‐0.88, P < 0.01). On adjusted analysis, neither BRAF nor MSI status were individually predictive of survival benefit. On adjusted analysis specifically of the chemotherapy effect in each subgroup, only patients in the presumed Lynch (HR 0.260, 95% CI, 0.09‐0.80, P < 0.01) and other BRAF groups (HR 0.45, 95% CI, 0.23‐0.87, P < 0.01) had a significant survival benefit from chemotherapy. On interaction testing of subgroups, adjusting for all the clinicopathological parameters, only patients in the presumed Lynch group (HR 0.277, 95% CI, 0.10‐0.75, P < 0.01) gained a differentially greater benefit from chemotherapy than other groups. Conclusions: In this historical cohort, MSI testing is predictive of response to adjuvant chemotherapy in stage III colon cancer, but only when results are interpreted in combination with BRAF . This supports the role of routine testing for these biomarkers.